Synthesis of chroman-4-ones by Reduction of Chromones - Semeniuchenko, Volodymyr; Groth, Ulrich; Khilya, Volodymyr (Current Organic Synthesis, 2010)
The articles which report about the synthesis of chroman-4-ones by hydrogenation/reduction of the corresponding chromones are reviewed. The following methods of synthesis are reviewed: hydrogenation over palladium, platinum, Raney-nickel, catalytic transfer hydrogenation, homogeneous hydrogenation, reduction by complex hydrides, by DIBALH and some special methods. For every appropriate reaction yield, the duration and some additional information is given (if available). Moreover, many exceptions and interesting transformations are described.
Keywords: Heterocycles